The Water Quality Status of Kupang Tilong Dam Reported by the Pollution Index Parameters - Nurlailah D. Kartika; Suwari; Luther Kadang (Journal of Applied Chemical Science, 2013)
There has been reported the water quality status of Kupang Tilong Dam using pollution index parameters. The water samples were taken from five stations and determined using purposive sampling method. The pollution index parameters analyzed were temperature, pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), total solid suspended (TSS), N-nitrate, P-phospate, and water discharge. The results showed that temperature and pH were 25-28.5ºC and 7.54-7.61 pH units, respectively, while the DO, BOD, COD, TSS, N-nitrate, and P-phosphate values (in mg/L) were 8.26-12.5, 1.63-3.04, 11.26-47.37, 4.73-6.28, 0.019-0.043, and 0.01-0.16 mg/L, respectively. The pollution loads detected on station I within water discharges of 250 m3/s could receive the BOD, COD and TSS loads by 236.67, 3681.16, and 488.52 tons/year, respectively. While the station II within water discharges of 0.15 m3/s could receive 126783.01, 2210094.72, and 290587.56 tons/year, respectively. Those results indicated that the water quality status of Kupang Tilong Dam is in a state between a good quality up to a slight polluted that was 0.80 to 3.18 of pollution index value.